Information and operational technology security systems : first International Workshop, IOSec 2018, CIPSEC Project, Heraklion, Crete, Greece, September 13, 2018, Revised Selected Papers /: first International Workshop, IOSec 2018, CIPSEC Project, Heraklion, Crete, Greece, September 13, 2018, Revised Selected Papers. (2019) - Unknown
No abstract available